2008
DOI: 10.1111/j.1369-1600.2008.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Blocking cannabinoid CB1 receptors for the treatment of nicotine dependence: insights from pre‐clinical and clinical studies

Abstract: Tobacco use is one of the leading preventable causes of death in developed countries. Since existing medications are only partially effective in treating tobacco smokers, there is a great need for improved medications for smoking cessation. It has been recently proposed that cannabinoid CB 1 receptor antagonists represent a new class of therapeutic agents for drug dependence, and, notably, nicotine dependence. Here, we will review current evidence supporting the use of this class of drugs for smoking cessation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 121 publications
(153 reference statements)
4
71
0
Order By: Relevance
“…The CB 1 inverse agonist rimonabant, in addition to serving as an antagonist in pharmacological studies of cannabinergic drugs, showed initial promise as a novel type of therapeutic for appetitive suppression and smoking cessation (Pacher et al, 2006;Padwal and Majumdar, 2007;Le Foll et al, 2008;Rigotti et al, 2009). However, reports of gastrointestinal side effects and mood-depressant actions (Després et al, 2005;Van Gaal et al, 2005;Traynor, 2007) cut short its use in clinical populations, leaving the future development of this class of drugs in doubt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CB 1 inverse agonist rimonabant, in addition to serving as an antagonist in pharmacological studies of cannabinergic drugs, showed initial promise as a novel type of therapeutic for appetitive suppression and smoking cessation (Pacher et al, 2006;Padwal and Majumdar, 2007;Le Foll et al, 2008;Rigotti et al, 2009). However, reports of gastrointestinal side effects and mood-depressant actions (Després et al, 2005;Van Gaal et al, 2005;Traynor, 2007) cut short its use in clinical populations, leaving the future development of this class of drugs in doubt.…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical perspective, rimonabant has also been shown to have beneficial effects in the management of obesity and smoking cessation, presumably as a result of its antagonist actions (Pacher et al, 2006;Padwal and Majumdar, 2007;Le Foll et al, 2008;Rigotti et al, 2009). Unfortunately, numerous reports describing gastrointestinal side effects such as nausea and emesis as well as mooddepressant actions followed the introduction of rimonabant, hampering its utility and eventually resulting in its removal from clinical practice (Després et al, 2005;Van Gaal et al, 2005;Traynor, 2007).…”
mentioning
confidence: 99%
“…Nicotine-induced increases in VTA 2-AG formation (14) likely contribute to the well-documented CB 1 receptor influence on behavioral and physiological response to nicotine (25). In the VTA, CB 1 receptors are thought to dynamically regulate GABA release at DAergic synapses (4), allowing the possibility that 2-AG formation dampens GABAergic constraint of DA cell excitation.…”
Section: Discussionmentioning
confidence: 99%
“…The resultant decrease in DA cell excitability likely underlies the ability of CB 1 antagonists to block nicotine-induced increases in nucleus accumbens DA release and to suppress nicotine self-administration (25,(29)(30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that at least some actions of nicotine are mediated indirectly through the action of endocannabinoids [17]. For instance, endocannabinoid levels are increased in the limbic forebrain of rats chronically treated with nicotine [18].…”
Section: Page 4 Of 33mentioning
confidence: 99%